Tính tổng sau: (x ²y – 3xy ³ + 5xy) + (3x ²y + 3xy ³ – 2xy)

Question

Tính tổng sau:
(x ²y – 3xy ³ + 5xy) + (3x ²y + 3xy ³ – 2xy)

in progress 0
Sapo 1 tháng 2021-05-16T04:13:26+00:00 2 Answers 4 views 0

Answers ( )

  1. `(x^2y -3xy^3 + 5xy) + ( 3x^2y + 3xy^3 – 2xy)`

    `= x^2y – 3xy^3 + 5xy+3x^2y + 3xy^3 – 2xy`

    `= (x^2y + 3x^2y) – (3xy^3 – 3xy^3) + (5xy – 2xy)`

    `= 4x^2y + 3xy`

     

  2. Đáp án:

     

    Giải thích các bước giải:

    (x ²y – 3xy ³ + 5xy) + (3x ²y + 3xy ³ – 2xy)

    ⇔x ²y – 3xy ³ + 5xy + 3x ²y + 3xy ³ – 2xy

    ⇔4x ²y +3xy

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )